Dependencies are more psychologically plausible, not more parsimonious - Hudson, Richard (Language Under Discussion, 2018)
I argue that the crucial criterion for evaluating analyses is psychological plausibility, and not parsimony, so the number of nodes isn’t important—and indeed, one version of dependency analysis recognises as many nodes as some phrase-structure analyses do. But in terms of plausibility, dependency grammar is preferable to phrase structure because the latter denies that the human mind is capable of recognising direct links (dependencies) between words.